Shifts in the Dynamics of the Global Financial System: Implications for Macroprudential Policy in the Digital Era - BQ. Elok Nirwana; Padli Pawaid Yahya; Lina Azizah (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This article examines the implications of the transformation of the global financial system on the implementation of macroprudential policy in the digital era, particularly during the period from 2019 to 2023. The study is motivated by the rapid development of financial globalization, deregulation policies, and technological innovation that have fundamentally reshaped the structure and dynamics of the global financial landscape. These developments have created significant opportunities, including broader access to funding sources, accelerated cross-border capital flows, improved financial inclusion, and deeper integration of international financial markets. However, at the same time, these structural changes have also introduced increasingly complex systemic risks, such as heightened financial interconnectedness, vulnerability to digital disruptions, cyber risks, market volatility, and the emergence of new financial actors driven by financial technology innovation. This research employs a descriptive qualitative approach through the analysis of literature, policy developments, and recent trends in the global financial system. The findings reveal that the rapid growth of digital finance has transformed economic behavior, financial institutions, and market structures, creating new challenges for financial regulation and supervision. Therefore, macroprudential policies need to become more adaptive and responsive in addressing emerging digital risks. The study highlights the importance of stronger regulatory coordination, effective monitoring systems, and innovative policy strategies to maintain sustainable financial stability in an increasingly dynamic global financial environment.